Isabelle Maynard: capstone - Maynard, Isabelle, artist (Colorado State University. Libraries, 2025)
The artist's statement: My paintings are rooted in memory: personal, fragmented and often distorted by time and emotion. I use my art to explore how moments from the past linger and resurface—not always as they happened, but as they felt. I interpret these recollections through a surreal lens, shifting and distorting objects and figures to reflect the visceral intensity of each memory. I primarily work with oil paint on canvas, using a layering and glazing technique that enhances the color and depth of the environment. This method allows me to create an atmospheric glow to my pieces, creating a rich and dramatic color palette. My process begins with a mental recollection of a memory. Even if the details are not accurate to real events, I build the painting around the feeling and let it evolve naturally as I work. Each painting I make is a way of reclaiming historical spaces by manifesting the emotional responses those spaces evoke. Painting allows me to assert my presence and narrate my experiences through a visual language. My work does not represent the past with precision, but rather captures how memory feels—often hazy, surreal, and emotionally heavy. My hope is that my work creates a space for reflection, both of self and shared experience.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting